Characterisation of a sucrose‐independent in vitro biofilm model of supragingival plaque. (18th October 2017) - Tsutsumi, K; Maruyama, M; Uchiyama, A; Shibasaki, K
Abstract : Objectives: Sugar consumption has been decreasing in Japan, suggesting higher rates of sucrose‐independent supragingival plaque formation. For developing an in vitro biofilm model of sucrose‐independent supragingival plaque, this study aimed to investigate the compositions and functions on contributing to cariogenicity in comparison with sucrose‐dependent biofilm. Materials and Methods: An in vitro multispecies biofilm containing Actinomyces naeslundii, Streptococcus gordonii, S. mutans, Veillonella parvula and Fusobacterium nucleatum was formed on 24‐well plates in the absence or presence of 1% sucrose. Compositions were assessed by plate culture, scanning electron microscopy and confocal laser scanning microscopy after fluorescent in situ hybridisation or labelling of extracellular polymeric substances (EPS). Functions were assessed by acidogenicity, adherence strength and sensitivities to anticaries agents. Results: Although both biofilms exhibited a Streptococcus predominant bacterial composition, there were differences in bacterial and EPS compositions; in particular, little glucan EPS was observed in sucrose‐independent biofilm. Compared with sucrose‐dependent biofilm, acidogenicity, adherence strength and antimicrobial resistance of sucrose‐independent biofilm were only slightly lower. However, dextranase degradation was substantially lower in sucrose‐independent biofilm. Conclusion: Our findings suggest that sucrose‐independent biofilm may have cariogenicity as with sucrose‐dependent biofilm. These in vitro models can help further elucidate plaque‐induced caries aetiology and develop new anticaries agents.